2008
DOI: 10.1111/j.1365-3040.2008.01883.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of MYB transcription factor: PvPHR1 and microRNA: PvmiR399 in phosphorus‐deficiency signalling in common bean roots

Abstract: Phosphorus (P), an essential element for plants, is one of the most limiting nutrients for plant growth. A few transcription factor (TF) genes involved in P-starvation signalling have been characterized for Arabidopsis thaliana and rice. Crop production of common bean (Phaseolus vulgaris L.), the most important legume for human consumption, is often limited by low P in the soil. Despite its agronomic importance, nothing is known about transcriptional regulation in P-deficient bean plants. We functionally chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 47 publications
4
161
0
1
Order By: Relevance
“…To create the PvPI3K-RNAi construct, a 537-bp fragment corresponding to the 39-coding region of Pv-PI3K was amplified by PCR using the primers PvPI3K-RNAi_F and PvPI3K-RNAi_R (Supplemental Table 1) and cDNA from P. vulgaris nodules (20 dai). After cloning this fragment into pENTR/D-TOPO (Invitrogen) and confirming the presence of the insert by sequencing, the PCR product was recombined into the compatible recombination sites of the Gateway-based hairpin pTDT-DC-RNAi vector (Valdés-López et al, 2008). The correct orientation of the recombined fragments was confirmed by sequencing and by PCR using the primers Wrky-3_F or Wrky-5_R with PvPI3K-RNAi_F (Supplemental Table 1), as described (Valdés-López et al, 2008).…”
Section: Vector Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…To create the PvPI3K-RNAi construct, a 537-bp fragment corresponding to the 39-coding region of Pv-PI3K was amplified by PCR using the primers PvPI3K-RNAi_F and PvPI3K-RNAi_R (Supplemental Table 1) and cDNA from P. vulgaris nodules (20 dai). After cloning this fragment into pENTR/D-TOPO (Invitrogen) and confirming the presence of the insert by sequencing, the PCR product was recombined into the compatible recombination sites of the Gateway-based hairpin pTDT-DC-RNAi vector (Valdés-López et al, 2008). The correct orientation of the recombined fragments was confirmed by sequencing and by PCR using the primers Wrky-3_F or Wrky-5_R with PvPI3K-RNAi_F (Supplemental Table 1), as described (Valdés-López et al, 2008).…”
Section: Vector Constructionmentioning
confidence: 99%
“…A specific PvPI3K-RNAi construct (537 bp) was cloned downstream of the 35S promoter sequence in the Gateway-based hairpin vector pTdT-DC-RNAi (Valdés-López et al, 2008) to generate pTdT-PvPI3K-RNAi. A previously described construct bearing a truncated and irrelevant sequence from Arabidopsis pre-mir159 cloned in pTdT-DC-RNAi (Montiel et al, 2012) was used as a control vector and is herein referred to as pTdT-Sac-RNAi.…”
Section: Downregulation Of Pi3k Affects Root Hair Growth and Curling mentioning
confidence: 99%
“…The transformations were conducted using a modified version of the binary vector backbone pNB96 (pSC218; Curtin et al, 2011) with an introduced inverted-repeat cassette to facilitate cloning of hairpin RNA fragments (pSC218GH) and a reading-frame cassette to incorporate both the Cas9 and target guide RNA entry vectors (pSC218GG). The inverted-repeat and reading-frame cassettes were derived from previously reported pTDT-DC-RNAi and pTDTO vectors (Valdés-López et al, 2008) and were driven by the constitutively expressed Glycine max Ubiquitin promoter (Hernandez-Garcia et al, 2010).…”
Section: Hairpin and Crispr/cas9 Transgenes And Whole-plant Transformmentioning
confidence: 99%
“…PvPHR1 is supposed to be positive regulator of genes implicated in transport, mobilization and homeostasis of phosphorus. Valdés-López et al (2008) demonstrated that miRNA399 of P. vulgaris (PvmiR399) is an essential component of the PvPHR1 signalling pathway in common bean (P. vulgaris L.). Jones-Rhoades and Bartel (2004) have indicated that miR395 and miR399 are up-regulated when plants suffer from sulphur and phosphate starvation in Arabidopsis.…”
Section: Abiotic Stress Tolerancementioning
confidence: 99%